The impact of electronic decision support and electronic remote blood issue on transfusion practice - Hibbs, S; Noel, S; Miles, D; Staves, J; Murphy, M (Wiley, 2014)
Objectives: To assess the impact on transfusion practice of a two-stage electronic intervention: the introduction of a decision support system (DSS) followed by the addition of electronic remote blood issue (ERBI). Background: With increasing evidence to show the benefit of restrictive transfusion policies, it is important to ascertain which interventions can increase clinician compliance with their implementation. A DSS provides patient-specific recommendations to clinicians. ERBI reduces delays in acquiring blood and may alter the transfusion behaviour of clinicians. Methods: All electronically requested blood transfusions administered outside of surgical theatres or recovery were identified in an orthopaedic hospital. These were divided into three time periods corresponding to pre-intervention, the successive introduction of DSS alone and DSS with ERBI. Pre- and post-transfusion haemoglobin (Hb) concentration levels, and the number of units ordered and transfused were recorded. Results: A total of 204 transfusions for 92 patients were assessed; 38 of 85 (45%) transfusions in the first time period were compliant. This did not significantly change after introduction of the DSS, but with DSS and ERBI together significantly increased to 39 of 60 (65%) (Pand#60;0·05). Mean pre-transfusion Hb reduced from 8·24gdl-1 in the first time period to 7·67gdl-1 in the third (Pand#60;0·0001). There was no significant change in overall blood usage, although ERBI significantly reduced the amount of unused blood orders from 70 to 25%. Conclusion: Electronic DSS was not sufficient to change practice in the form implemented in this study. ERBI can contribute to significant improvements in blood usage as well as the efficiency of blood provision.